Comparing Response of Sheep and Cow Milk on Acute Digestive Comfort and Lactose Malabsorption: A Randomized Controlled Trial in Female Dairy Avoiders - Shrestha, Aahana; Samuelsson, Linda M.; Sharma, Pankaja; Day, Li; Cameron-Smith, David; Milan, Amber M. (Frontiers in Nutrition, 2021)
Background: Sheep milk (SM) is a possible alternate dairy source for those who experience digestive symptoms with cow milk (CM). While both the milks contain lactose, one of the causes for self-reported intolerance to cow milk, the composition of SM and CM also differs across proteins and fats, which have been shown to impact digestive processes. Objective: To compare the acute digestive comfort and lactose malabsorption of SM to CM in female dairy avoiders. Method: In a double-blinded, randomized cross over trial, 30 dairy-avoiding females (aged 20-30 years) drank 650 mL of SM or CM (each reconstituted from spray dried powder) following an overnight fast, on two separate occasions at least one week apart. Blood samples were collected for glucose and insulin assessment, and single nucleotide polymorphisms of the lactase (LCT) gene (C/T13910 and G/A22018). Breath H2 and visual analog scale (VAS) digestive symptom scores were recorded at fasting and regular intervals over 4 h after ingestion. Results: 80% of study participants were lactase non-persistent (LNP; CC13910 and GG22018 genotype). Digestive symptoms, including abdominal cramps, distension, rumbling, bloating, belching, diarrhoea, flatulence, vomiting, and nausea, were similar in response to SM and CM ingestion (milk × time, P > 0.05). Breath H2 was greater after CM than SM (72 ± 10 vs. 43 ± 6 ppm at 240 min, P < 0.001), which may be due to greater lactose content in CM (33 vs 25 g). However, when corrected for the lactose content breath H2 did not differ between the two milks. The response remained similar when analyzed in the LNP subset alone (n=20). Conclusions Despite a higher energy and nutrient content, SM did not increase adverse digestive symptoms after ingestion, relative to CM, although there was a reduced breath H2 response, which could be attributed to the lower lactose content in SM. The tolerability of SM should be explored in populations without lactose intolerance for whom underlying trigger for intolerance is unknown.